Preparation method of copper-doped amorphous titanium dioxide electrochemical nitrate reduction catalyst
By doping copper in the electrocatalyst and using an amorphous titanium dioxide support, an efficient electrocatalyst was prepared, which solved the problems of low ammonia synthesis yield and poor catalyst stability in the prior art, and achieved efficient and stable ammonia synthesis.
Patent Information
- Application Number
- CN202411277059.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-12
- Publication Date
- 2025-03-07
AI Technical Summary
The existing electrochemical nitrogen and nitrate reduction and synthesis of ammonia technology has problems such as low yield, low energy efficiency and poor catalyst stability, which is difficult to replace the traditional Haber method.
Copper-doped amorphous titanium dioxide is used as an electrocatalyst, and a specific preparation method includes adding titanium-containing compound and phosphoric acid to the alcohol-containing solvent, followed by adding ammonia water and a copper-containing compound. After stirring, washing, drying and calcining, copper-doped amorphous titanium dioxide nanomaterial is prepared.
The nitrate reduction activity and stability of the electrocatalyst are significantly improved, and efficient ammonia synthesis is achieved, the ammonia yield is significantly improved, and the electrochemical performance of the catalyst is excellent.
Smart Images

Figure CN119571371A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of nano material design and synthetic ammonia, and in particular to a method for preparing a copper-doped amorphous titanium dioxide electrochemical nitrate reduction catalyst. Background Art
[0002] Ammonia (NH3) is a raw material for the production of a series of nitrogen-containing chemicals such as nitric acid, organic nitrogen compounds, urea, and amino acids. The current industrial ammonia production mainly relies on the fossil fuel-driven Haber-Bosch process, which consumes global energy and emits a large amount of carbon dioxide. The development of green and mild ammonia synthesis technology is of great research significance. Using nitrogen as a nitrogen source, the synthesis of ammonia through electrochemical reduction reaction is expected to replace the Haber-Bosch process, but the N≡N triple bond dissociation energy is high and the solubility of nitrogen in water is low. In addition, due to low yield and potential contamination from different sources, the quantification of ammonia in the electrochemical nitrogen reduction synthesis reaction is still challenging.
[0003] Nitrate, as one of the environmental water pollutants, contains nitrate (NO 3- ) has a lower N=O bond energy, and NO 3- The solubility in aqueous solution is higher, and the electrochemical reduction of nitrate is more thermodynamically favorable, making it a suitable nitrogen source for electrically driven NH3 synthesis under ambient conditions. However, the eight-electron reduction process of nitrate reduction to synthesize ammonia is complex, and electrocatalysts are required to reduce overpotential and improve energy efficiency and conversion efficiency. The design and construction of electrocatalysts and the exploration of their catalytic mechanisms are crucial in improving the performance of synthetic ammonia. The exploration of high-performance electrocatalysts is of far-reaching significance for the construction of an efficient and environmentally friendly synthetic ammonia system.
[0004] The weak nitrate adsorption capacity of noble metal catalysts such as Pt and Pd leads to a generally slow reduction rate and low ammonia yield. Based on molecular orbital theory, the transition metal Cu has a similar highest occupied molecular orbital (HOMO, d orbital) as nitrate, which means that Cu easily injects electrons into the NO bond of nitrate, making copper-based catalysts have excellent nitrate conversion activity. In addition, Cu has a stronger affinity for nitrate than active hydrogen, and the lower hydrogen coverage inhibits the reaction between adsorbed hydrogen atoms to produce H2. Although Cu-based catalysts have been reported, metal-based catalysts are often prone to oxidative dissolution, leaching and surface poisoning, resulting in decreased electrochemical activity and stability. How to maintain the stability of copper metal sites and effectively avoid agglomeration and dissolution during the electrochemical reaction remains to be studied, and the electrochemical ammonia synthesis activity of copper-based catalysts needs to be improved. Summary of the invention
[0005] In order to solve the above problems, the present invention discloses a method for preparing a copper-doped amorphous titanium dioxide electrochemical nitrate reduction catalyst, which is characterized by comprising the following steps: In the first step, a compound containing titanium is added to an alcohol-containing solvent; In the second step, phosphoric acid is added to the mixed solution of the first step, and after the reaction, the mixture is washed, dried, and calcined in a muffle furnace to obtain an amorphous titanium dioxide nanomaterial; The third step is to add the amorphous titanium dioxide nanomaterial into the aqueous solution, and then add ammonia water and a copper-containing compound in sequence, stir at room temperature, wash, dry, and calcine in a muffle furnace to obtain the copper-doped amorphous titanium dioxide nanomaterial.
[0006] Preferably, the titanium-containing compound is any one or two of titanium tetrachloride, titanium sulfate, tetrabutyl titanate, and isopropyl titanate, and the alcohol is any one or two of methanol, ethanol, ethylene glycol, and 1,2-propylene glycol.
[0007] Preferably, in the second step, the volume ratio of the acid to the alcohol is 1:10 to 1:100, and the molar concentration of titanium in the alcohol is 0.05 to 1 mol L -1 , the reaction time is 12 to 48 h, the muffle furnace calcination temperature is 250 to 450 °C, and the muffle furnace calcination time is 1 to 5 h.
[0008] Preferably, in the third step, the molar concentration of titanium dioxide in the aqueous solution is 0.03 to 0.5 mol L -1 The volume ratio of ammonia water to water is 1:10 to 1:50, preferably 1:20.
[0009] Preferably, in the third step, the compound containing the copper element is any one or two of copper nitrate, copper chloride, copper acetate and copper sulfate.
[0010] Preferably, in the third step, the molar ratio of copper element to titanium dioxide is 1:10 to 1:100.
[0011] Preferably, in the third step, the stirring time at room temperature is 8 to 25 h, the calcination temperature in the muffle furnace is 250 to 500 °C, and the calcination time in the muffle furnace is 1 to 5 h. A use as a catalyst for electrochemical nitrate reduction ammonia synthesis, the catalyst is prepared by the above preparation method, the catalyst exhibits good electrocatalytic nitrate ammonia synthesis activity in an alkaline electrolyte, the nitrate is potassium nitrate or sodium nitrate, the alkali is potassium hydroxide or sodium hydroxide, and the molar concentration ratio of the nitrate to the alkali is 0.1:1 to 1:1.
[0012] Beneficial effects of the present invention: (1) Compared with carbon-based materials, amorphous oxides have more randomly oriented unsaturated bonds, which are conducive to the adsorption of reactants.
[0013] (2) A large number of surface defects (such as oxygen vacancies) on the surface of the amorphous phase carrier can effectively disperse and stabilize the metal sites, and NO3− can be easily captured and fixed at the defect sites, inhibiting the migration of N-intermediates and their coupling.
[0014] (3) Amorphous titanium oxide is coupled with transition metal copper. By leveraging the synergistic effect between the defect-rich amorphous titanium oxide support and the highly dispersed metal sites, the catalytic environment and action mechanism on the electrocatalyst surface are significantly optimized, thus achieving the design and construction of high-performance nitrate reduction electrocatalysts.
[0015] (4) The catalyst preparation method is simple and easy to prepare on a large scale. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 is the X-ray diffraction pattern of the catalyst of Example 1 of the present invention; Figure 2 is a transmission electron microscope image of the catalyst of Example 1 of the present invention; Figure 3 It is a transmission electron microscope image of the catalyst of Comparative Example 2 of the present invention. DETAILED DESCRIPTION
[0017] The present invention is further explained below in conjunction with the accompanying drawings and specific embodiments. It should be understood that the following specific embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention. It should be noted that the words "front", "rear", "left", "right", "upper" and "lower" used in the following description refer to directions in the accompanying drawings, and the words "inner" and "outer" refer to directions toward or away from the geometric center of a specific component, respectively. Example 1
[0018] 1.5 mL of tetrabutyl titanate was added to 15 mL of ethanol solution, stirred and dispersed evenly, 0.45 mL of phosphoric acid was added to the above mixture, stirred and reacted at room temperature for 24 h, washed with water and filtered, dried in an oven at 60 ° C overnight, and calcined in a muffle furnace at 400 ° C for 4 h to obtain amorphous titanium dioxide nanomaterials. After 0.1 g of amorphous TiO2 prepared above was uniformly dispersed in 30 mL of aqueous solution, 1 mL of ammonia water and 7 mg of copper nitrate were added in sequence, stirred at room temperature for 17 hours, centrifuged, washed with deionized water, dried in an oven overnight, and then calcined in a muffle furnace at 400 ° C for 2 h to obtain copper-doped amorphous titanium dioxide. Example 2
[0019] 2.5 mL of isopropyl titanate was added to 15 mL of ethanol solution, stirred and dispersed evenly, 0.3 mL of phosphoric acid was added to the above mixture, stirred and reacted at room temperature for 24 h, washed with water and filtered, dried in an oven at 60 ° C overnight, and calcined in a muffle furnace at 350 ° C for 4 h to obtain amorphous titanium dioxide. After 0.1 g of amorphous TiO2 prepared above was uniformly dispersed in 30 mL of aqueous solution, 1 mL of ammonia water and 6 mg of copper chloride were added in sequence, stirred at room temperature for 20 hours, centrifuged, washed with deionized water, dried in an oven overnight, and then calcined in a muffle furnace at 400 ° C for 2 h to obtain copper-doped amorphous titanium dioxide. Example 3
[0020] 6 mL of titanium sulfate was added to 40 mL of ethanol solution, stirred and dispersed evenly, 0.8 mL of phosphoric acid was added to the above mixture, stirred and reacted at room temperature for 24 h, washed with water and filtered, dried in a 60°C oven overnight, and calcined in a muffle furnace at 400°C for 2 h to obtain amorphous titanium dioxide. 0.2 g of amorphous TiO2 prepared above was evenly dispersed in 60 mL of aqueous solution, and 2 mL of ammonia water and 10 mg of copper sulfate were added in sequence. After stirring at room temperature for 18 hours, centrifuged, washed with deionized water, dried in an oven overnight, and calcined in a muffle furnace at 400°C for 3 h to obtain copper-doped amorphous titanium dioxide. Example 4
[0021] 2 mL of titanium tetrachloride was added to 33 mL of ethanol solution, stirred and dispersed evenly, 0.5 mL of phosphoric acid was added to the above mixture, stirred at room temperature for 18 h, washed with water and filtered, dried overnight in a 60°C oven, and calcined at 400°C in a muffle furnace for 4 h to obtain amorphous titanium dioxide nanomaterials. 0.1 g of amorphous TiO2 prepared above was uniformly dispersed in 30 mL of aqueous solution, 1 mL of ammonia water and 14 mg of copper nitrate were added in sequence, stirred at room temperature for 18 hours, centrifuged, washed with deionized water, dried overnight in an oven, and then calcined at 400°C in a muffle furnace for 2 h to obtain copper-doped amorphous titanium dioxide. Example 5
[0022] 14 mL of tetrabutyl titanate was added to 90 mL of ethanol solution, stirred and dispersed evenly, 2 mL of phosphoric acid was added to the above mixture, stirred and reacted at room temperature for 24 h, washed with water and filtered, dried in a 60°C oven overnight, and calcined in a muffle furnace at 400°C for 4 h to obtain amorphous titanium dioxide nanomaterials. After 0.1 g of amorphous TiO2 prepared above was uniformly dispersed in 30 mL of aqueous solution, 1 mL of ammonia water and 14 mg of copper nitrate were added in sequence, stirred at room temperature for 17 hours, centrifuged, washed with deionized water, dried in an oven overnight, and then calcined in a muffle furnace at 400°C for 2 h to obtain copper-doped amorphous titanium dioxide.
[0023] 1.5 mL of tetrabutyl titanate was added to 15 mL of ethanol solution and stirred to disperse evenly. 0.45 mL of phosphoric acid was added to the mixture and stirred at room temperature for 24 h. After washing and filtering, the mixture was dried in an oven at 60 °C overnight and calcined in a muffle furnace at 400 °C for 4 h to obtain amorphous titanium dioxide nanomaterials. Comparative Example 2
[0024] After 0.1 g of commercial TiO2 was uniformly dispersed in 30 mL of aqueous solution, 1 mL of ammonia water and 7 mg of copper nitrate were added in sequence. After stirring at room temperature for 17 hours, the mixture was centrifuged, washed with deionized water, dried in an oven overnight, and then calcined at 400 °C in a muffle furnace for 2 h. Comparative Example 3
[0025] The patent subject is "A metal M-doped titanium dioxide photocatalyst and its application in photocatalytic ammonia fixation", with application number "202011377448.7". Table 1 in the embodiment shows that the ammonia production of Cu-TiO2 catalyst is 78.9 μmol·g -1 催化剂 ·h -1 , after conversion, it is approximately 1.34 mg·h -1 mg -1 催化剂 .
[0026] Electrochemical test: 5 mg of the catalyst prepared above was dispersed in a mixed solution containing 500 µL of ethanol and 400 µL of water, and 10 µL of Nafion solution was added. After ultrasonic treatment for 1 hour, 10 μL of the above dispersion was added dropwise to a 5 mm diameter glassy carbon electrode and dried naturally. The electrochemical test was carried out using an H-type electrolytic cell, in which the working electrode was the glassy carbon electrode prepared above, the reference electrode was an Ag / AgCl electrode, and the counter electrode was a Pt sheet. The counter electrode was located in the anode chamber, and the reference electrode and the working electrode were located in the cathode chamber, separated by an ion exchange membrane. Under an inert atmosphere, the time-current curve at a specified potential was tested, the voltage test interval was -1 V wave sign -0.1 V (compared to the reversible hydrogen electrode), the test time was 0.5 h, the electrolyte after the reaction was taken out from the cathode cell, and the ammonia in the reaction solution was quantified by the indophenol blue colorimetric method.
[0027] 1) Ammonia yield calculation formula: n: NH3 concentration measured by indophenol blue method (μg mL -1 ), V: Volume of electrolyte in the electrolytic cell (mL) t: reaction time (h) A: Area of glassy carbon electrode (cm 2 ).
[0028] 2) Calculation formula of Faradaic efficiency (FE): F: Faraday constant (96485 C mol -1 ) n: number of electrons gained or lost c: NH3 concentration (g mL -1 ) V: electrolyte volume (mL) M: relative molecular mass of ammonia (g mol -1 ) Q: Total power Q (C).
[0029] 3) X-ray diffractometer was used to characterize the phase composition of Example 1 and Comparative Example 1, as shown in FIG. Figure 1 As shown, the horizontal axis is the diffraction angle and the vertical axis is the diffraction peak intensity. The results show that there are no obvious characteristic peaks of titanium dioxide and copper metal. Figure 1 same.
[0030] 4) Figure 2 and Figure 3The transmission electron microscope image shown in the figure shows that when amorphous titanium dioxide is used as a carrier to load copper, there are no obvious agglomerated nanoparticles on the carrier surface, while the comparative sample using commercial titanium dioxide as a carrier has obvious agglomerated particles on the surface, which reflects the important role of amorphous titanium dioxide in dispersing metals. Figure 1 same.
[0031] Table 1 Performance results of electrochemical ammonia synthesis Example <![CDATA[Ammonia production rate / mg·h -1 ·mg -1 催化剂 > Embodiment 01 5.8 Embodiment 02 5.5 Embodiment 03 5.4 Embodiment 04 4.9 Embodiment 05 6.2 Comparative Example 1 3 Comparative Example 2 1.5 Comparative Example 3 1.34 <![CDATA[TiO2]]> 0.1
[0032] 5) Electrocatalytic test As shown in Table 1, the results show that the ammonia yield of Examples 1-5 at -1.0 V vs. RHE is as high as 6.2 mg h -1 mg -1 催化剂 , which is much higher than pure amorphous titanium dioxide and commercial TiO2, illustrating the important role of copper metal doping in improving electrochemical performance.
[0033] It can be seen from the above examples that by using amorphous titanium dioxide as a carrier, a highly dispersed copper-based electrocatalyst can be prepared, and the design and construction of an electrochemical nitrate reduction catalyst for ammonia synthesis under mild conditions is realized, showing excellent performance and potential application value.
[0034] The technical means disclosed in the scheme of the present invention are not limited to the technical means disclosed in the above-mentioned implementation mode, but also include technical schemes composed of any combination of the above technical features.
Claims
1. A method for preparing a copper-doped amorphous titanium dioxide electrochemical nitrate reduction catalyst, characterized in that: The following steps are involved: In the first step, a compound containing titanium is added to an alcohol-containing solvent; In the second step, phosphoric acid is added to the mixed solution of the first step, and after the reaction, the mixture is washed, dried, and calcined in a muffle furnace to obtain an amorphous titanium dioxide nanomaterial; The third step is to add the amorphous titanium dioxide nanomaterial into the aqueous solution, and then add ammonia water and a copper-containing compound in sequence, stir at room temperature, wash, dry, and calcine in a muffle furnace to obtain the copper-doped amorphous titanium dioxide nanomaterial.
2. The method for preparing a copper-doped amorphous titanium dioxide electrochemical nitrate reduction catalyst according to claim 1, characterized in that: The titanium-containing compound is any one or two of titanium tetrachloride, titanium sulfate, tetrabutyl titanate, and isopropyl titanate, and the alcohol is any one or two of methanol, ethanol, ethylene glycol, and 1,2-propylene glycol.
3. The method for preparing a copper-doped amorphous titanium dioxide electrochemical nitrate reduction catalyst according to claim 1, characterized in that: In the second step, the volume ratio of the acid to the alcohol is 1:10 to 1:100, and the molar concentration of titanium in the alcohol is 0.05 to 1 mol L -1 , the reaction time is 12 to 48 h, the muffle furnace calcination temperature is 250 to 450 °C, and the muffle furnace calcination time is 1 to 5 h.
4. The method for preparing a copper-doped amorphous titanium dioxide electrochemical nitrate reduction catalyst according to claim 1, characterized in that: In the third step, the molar concentration of titanium dioxide in the aqueous solution is 0.03 to 0.5 mol L -1 , the volume ratio of ammonia water to water is 1:10 to 1:
50.
5. The method for preparing a copper-doped amorphous titanium dioxide electrochemical nitrate reduction catalyst according to claim 1, characterized in that: In the third step, the compound containing copper element is any one or two of copper nitrate, copper chloride, copper acetate and copper sulfate.
6. The method for preparing a copper-doped amorphous titanium dioxide electrochemical nitrate reduction catalyst according to claim 1, characterized in that: In the third step, the molar ratio of copper element to titanium dioxide is 1:10 to 1:
100.
7. The method for preparing a copper-doped amorphous titanium dioxide electrochemical nitrate reduction catalyst according to claim 1, characterized in that: In the third step, the stirring time at room temperature is 8 to 25 hours, the calcination temperature in the muffle furnace is 250 to 500° C., and the calcination time in the muffle furnace is 1 to 5 hours.
8. An application as a catalyst for electrochemical nitrate reduction to synthesize ammonia, characterized in that: The catalyst is prepared by the preparation method described in claims 1-7, and the catalyst exhibits good electrocatalytic nitrate synthesis of ammonia activity in an alkaline electrolyte. The nitrate is potassium nitrate or sodium nitrate, the alkali is potassium hydroxide or sodium hydroxide, and the molar concentration ratio of the nitrate to the alkali is 0.1:1 to 1:1.
Citation Information
Patent Citations
Metal M-doped titanium dioxide photocatalyst and application thereof in photocatalytic nitrogen fixation
CN112642427A